2012
DOI: 10.1002/anie.201201283
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Catalytic Structure of Gold Nanoparticles Supported on TiO2

Abstract: Despite the fragility of TiO(2) under electron irradiation, the intrinsic structure of Au/TiO(2) catalysts can be observed by environmental transmission electron microscopy. Under reaction conditions (CO/air 100 Pa), the major {111} and {100} facets of the gold nanoparticles are exposed and the particles display a polygonal interface with the TiO(2) support bounded by sharp edges parallel to the 〈110〉 directions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
103
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(111 citation statements)
references
References 41 publications
6
103
0
Order By: Relevance
“…Reprinted from Ref. [46] with permission by Wiley-VCH; (d) catalytic active atoms of gold nanoparticles supported on CeO 2 characterized by ETEM. Reprinted from Ref.…”
Section: Gold Supported On Rmomentioning
confidence: 99%
See 1 more Smart Citation
“…Reprinted from Ref. [46] with permission by Wiley-VCH; (d) catalytic active atoms of gold nanoparticles supported on CeO 2 characterized by ETEM. Reprinted from Ref.…”
Section: Gold Supported On Rmomentioning
confidence: 99%
“…At higher temperatures, CO molecules adsorbed on Au sites become active and participated in the reaction. By environmental TEM (ETEM) observations, Takeda's group [45][46][47] found that adsorbed CO molecule could induce reconstruction of Au (1 0 0) facet, which led to the on-top adsorption of CO on the gold atoms of GNPs (2-5 nm) supported on CeO 2 [45,47] or TiO 2 [46] at room temperature (Fig. 1c).…”
Section: Gold Supported On Rmomentioning
confidence: 99%
“…For example, while contracting the beam at a constant total dose-rate has no effect on the resolution, it will increase the extent of beam-induced changes to the sample as these are reported to be determined primarily by the areal dose-rate [26][27][28][29][30]. Conversely, expanding the electron beam puts surrounding areas at risk for unintentional exposure and structural alterations.…”
Section: Resultsmentioning
confidence: 99%
“…By switching from one gas to another, a systematic change of the morphology can be observed in the majority of the nanoparticles [253][254][255][256]. Regarding the active phase/support interaction, it was observed that by increasing the electron dose D, the nanoparticles were increasingly decorated with material originating from the support.…”
Section: Importance Of the Support For The Stabilitymentioning
confidence: 99%
“…Another striking example of nanoparticle/support interaction is the structural reorganisation on the Au/TiO 2 system under beam irradiation [253]. The study was performed under vacuum, inert atmosphere (N 2 -100 Pa), oxygen atmosphere (O 2 -100 Pa) and reactive atmosphere (1 vol% CO in air-100 Pa).…”
Section: Importance Of the Support For The Stabilitymentioning
confidence: 99%